Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match oleh Guru PAK terhadap Keaktifan Belajar Siswa Kelas VIII SMP Negeri 2 Sipoholon Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2024)
The learning model really determines the success of learning, including students' active learning. This Research Aims To Determine The Effect of The Make A Match Type Cooperative Learning Model by PAK Teachers On The Active Learning of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 Academic Year. The method used in this research is a quantitative method, a type of pre-experimental approach with the design form